Research and evaluation methods in special education - Mertens, Donna M.; McLaughlin, John A. (Thousand Oaks, CA : Corwin Press ; Council for Exceptional Children, 2004)
This excellent resource provides an approach to research and evaluation that helps educators better understand and address the needs of students with various disabilities.
1. Introduction -- 2. Program evaluation -- 3. Literature review -- 4. Quantitative research methods: questions of impact -- 5. Other quantitative approaches: causal comparative, correlational, single-case and survey research -- 6. Qualitative methods -- 7. Mixed methods and mixed model designs -- 8. Identification and selection of research participants -- 9. Information collection -- 10. data analysis, interpretation and use.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION -- RESEARCH -- METHODOLOGY; CHILDREN WITH DISABILITIES -- EDUCATION -- RESEARCH -- METHODOLOGY; EDUCATIONAL EVALUATION